Proceedings of Selected Articles of 2013 World Agricultural Outlook Conference - Xu, Shiwei; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Food security has always been a major global concern and is getting more attention in recent years. In fact, the global economy and stability has been severely challenged by the precarious state of food security, which was exacerbated by a combination of sharp price volatility and disastrous weather conditions related to climate change. The book aims to improve the analysis and projection of agricultural production and marketing, facilitates information exchange to better food supply and demand, and ultimately contributes to enhance world food security and sustainable global agricultural development.
Construction of China Agriculture Monitoring and Early-warning System (CAMES) -- Design and Implementation of Agricultural Product Prices Short-Term Forecasting System -- Forecasting and Early-warning Research on the Price of China's Corn and Late Indica Rice -- Decomposition Study of the Agricultural Products Price Study on stabilizing price of hog market in China -- Research on the Optimal Combination Forecasting Model for Vegetable Price in Hainan -- Research and Design of Vegetable Price Spatial-temporal Transmission Simulation -- Food Consumption of Households in Poverty-stricken Areas of West China: The Case of Shaanxi, Yunnan, and Guizhou -- Analysis and Outlook of China’s Sugar Industry Development -- Perspective on the Trend of Soybean Production and Trade in China -- China's Aquatic Products Supply and Demand Situation over the Past Decade -- Spatial-Temporal Characteristics and Outlook of Grain Consumption in China -- Research on Early-warning Proposal of China Milk Market -- Meteorological Effects on China Expected Rapeseed Yield -- County-level Catastrophic Risk Assessment of Crops Caused by Flood in Northeast China -- Study on Fluctuation Rules of Meteorological Phenomena Stress Environment in Cow Dominant Areas in China -- Study on Extreme Risk Measurement of Chinese Soybean Futures Market — VaR Based on GARCH Model -- Prediction of Pork Prices Based on SVM -- Study on Optimal Risk Sharing Issue for Chinese Crop Insurance: A Case Study from Government Perspective -- Evaluating Catastrophe Risk of Cold Damage for Crop Production at the Provincial Scale in China -- Rice Yield of Rural Household of Niger State of Nigeria -- Study on Rural Microcredit Risk Management and Micro-Repayment Insurance -- Empirical Analysis on the Economies of Scale of Nature Rubber Production: Based on the Panel Data of 86 Rubber Farms of HSF between 1998-2007 -- Research on Economic Effect of Grain Consumption Expenditure in Urban and Rural China -- The Qualities and International Competitiveness of Livestock Products in the BRICs: A Comparative Analysis -- Study on the Evaluation Indexes for Asparagus Industrial Global Competitiveness -- The Analysis of Laminaria japonica Industry and International Trade Situation in China -- China’s Current Development Status and Prospect of Foxtail Millet Trade and Industry -- Preliminary Discussion on the Current Situations and Prospects of Cassava Starch Imports and Exports in China -- Monetary Policy and the Prices Volatility of Natural and Synthetic Rubber in China -- Analysis and Forecast of World Corn Market Trade and Policy -- Analysis on Current Fruit Market and Late Concerns in China -- Rice Policy Reviews in China, Thailand and Vietnam: Policy Instruments, Targets and Impacts -- Industrial agglomeration in China’s agricultural product processing industry -- Influence and Evaluation on Human Settlement Environment after Rural Homestead Consolidation in China: Evidence from the typical villages in Jiangsu Province -- A Study on Model Design of Tropical Agricultural Products Closed-loop Supply Chain in Hainan -- SWOT Analysis on industrial Development of Beijing Edible Fung -- Analysis on the technology application of traceability management for agro-product quality and safety in China -- Text segmentation model based LDA and ontology for Question Answering in Agriculture -- Research on Search Technology of Agricultural Information based on Geographical Perception -- Research of Construction of Australia Agriculture Information System -- An Analysis on the Trend of International Biomass Energy Technology -- Temporal Changes and the Influencing Factor of China Importing Genetic Resources of Livestock and Poultry -- Analysis of Major Factors Influencing Crop Yield of Shandong Province -- Study on Creative Agriculture Mode in Community -- The Application Study of Electronic Farming in the New Countryside Construction in Hainan -- Low Carbon Economy and Sustainable Development of Tropical Agriculture in Hainan Province.
Keywords: Agricultural economics; Agricultural Economics